Manifestasi Antroposentrisme pada Pengelolaan Sumber Daya Alam di Desa Satui Barat Kabupaten Tanah Bumbu - Rahmawati, Neli; Hamid, Ismar (Prodi Sosiologi FISIP ULM, 2025)
The phenomenon of environmental degradation in Satui Barat Village is closely linked to the exploitation of natural resources that prioritizes greater profits without considering ecological sustainability. This study aims to examine the manifestation of anthropocentrism in the management of natural resources in Satui Barat Village. The research employs a qualitative approach with a case study methodology. Data collection techniques include observation, interviews, and documentation. The findings indicate that the mindset of the Satui Barat community regarding natural resource management has been influenced by five characteristics of anthropocentrism. Anthropocentrism is a perspective that places humans at the center of everything, prioritizing human interests over environmental concerns. In the context of Satui Barat Village, economic activities, urbanization, and climate change also contribute to the well-being of the local community. Ideally, efforts to sustain human life should be balanced with sustainable environmental management, taking into account the long-term interests of both humans and nature. Anthropocentrism represents an ethical stance that neglects ecological balance and the sustainability of natural resources. In Satui Barat Village, mining activities have caused detrimental social impacts, such as forced evictions, land conflicts, and a decline in the quality of life for the local population. The current situation calls for changes in the governance of natural resources, placing greater emphasis on ecological sustainability to ensure a better and more sustainable quality of life. Coordinated efforts between the government, the mining industry, and local communities are essential to developing sustainable solutions that address the needs of all stakeholders, including environmental conservation. All sustainability efforts must be supported by a paradigm shift as a foundation, prioritizing environmental ethics that uphold quality and fairness for the entire ecosystem network.